Model of Sustainable Growth and Development of the Cableway Transport System in Slovenia - Težak, Sergej; Zelenika, Ratko; Sever, Drago (Promet - Traffic&Transportation, 2012)
The cableway transport system is very important for the Slovenian tourist economy. Within the Slovene transport system, the cableway transport subsystem has a specific role because it allows and ensures access to regions which are difficult to access or completely inaccessible by other transport subsystems owing to the configuration of the area. The quality and development of transport services are directly linked to the introduction of new cableways. New technical achievements, which are nowadays used in cableways, all provide greater capacity and higher speed of cableways, which, however, results in their higher maintenance and exploitation costs. The cableway transport system is being developed in Slovenia, but not on principles of sustainable development. This paper presents a model of sustainable growth and development of the cableway transport system in Slovenia based on which it is possible to determine assumptions for future growth so that the Slovene cableway transport system would approach standards of such highly developed systems. The new model includes ten essential elements of this system for which growth rates were calculated.